Longitudinal patterns of disordered eating behaviors in children and adolescents from the Brazilian High-Risk Cohort study for mental conditions - Iara Peixoto de Oliveira; Ana C. Fernandéz; Giovanni A. Salum; Ary Gadelha; Pedro Mario Pan; Eurípedes Constantino Miguel; Daniel C. Mograbi; Patricia Bado (Brazilian Journal of Psychiatry)
Objective: Disordered eating behaviors (DEB) are dysfunctional changes in eating behavior that do not meet the diagnostic criteria for eating disorders. DEB affect a significant percentage of individuals, yet the topic remains under-researched. The current study investigates the developmental trajectory and psychopathological correlates of DEB in children and adolescents in Brazil. Methods: The sample included 1,583 participants from the Brazilian High-Risk Cohort who were assessed across three waves between 2010 (age 6-12 years) and 2019 (age 12-21 years). Psychopathology was assessed through the Development and Well-Being Assessment, and DEB was assessed through Development and Well-Being Assessment’s eating disorder section. Dimensional psychopathology was measured with the Child Behavior Checklist. Results: The participants were divided into dysfunctional and non-dysfunctional eating groups. DEB varied significantly, with few participants having a persistent pattern. DEB were strongly linked to higher internalizing symptoms, especially in girls, but less to externalizing behaviors. DEB increased the likelihood of eating disorders, major depressive disorder, and higher body mass index. Conclusion: This study reveals that DEB are frequent among Brazilian children and adolescents and are linked to psychopathology (especially internalizing symptoms) and body mass index. Future research should investigate the underlying mechanisms of DEB and develop strategies for early detection and effective interventions.